American Indian English - Leap, William (University of Utah Press, 1993)
American Indian English documents and examines the diversity of English in American Indian speech communities. It presents a convincing case for the fundamental influence of ancestral American Indian languages and cultures on spoken and written expression in different Indian English codes. A distillation of over twenty years' research, this pioneering work explores the linguistic and sociolinguistic characteristics of English language use among members of Navajo, Hopi, Mojave, Ute, Tsimshian, Kotzebue, Ponca, Pima, Lakota, Cheyenne, Laguna, Santa Ana, Isleta, Chilcotin, Seminole, Cherokee, and other American Indian tribes. American Indian English fills numerous gaps in existing studies of language histories, Indian student school experience, Indian-white contact, and "acculturation." Unlike contemporary studies on schooling, ethnicity, empowerment, and educational failure, American Indian English avoids postmodernist jargon and discourse strategies in favor of direct description and commentary. Data are derived from conditions of real-life experience faced by speakers of Indian English in various English-speaking settings. This practical focus enhances the book's accessibility to Indian educators and community-based teachers, as well as non-Indian academics